Effects of Helicobacter pylori eradication on esophageal motility, esophageal acid exposure, and gastroesophageal reflux disease symptoms - Zhao, Tong; Liu, Fang; Li, Yongjun (Frontiers in Cellular and Infection Microbiology, 2023)
Background The effects of Helicobacter pylori (HP) eradication on gastroesophageal reflux disease (GERD) are yet to be fully elucidated. Few studies have investigated the mechanisms underlying the correlations between HP and GERD with prospective methods. The objective of this prospective clinical study was to explore the effects of HP eradication on GERD. Methods Patients diagnosed with both GERD and HP were included. High-resolution esophageal manometry (HRM), 24-h esophageal pH monitoring, and the Gastroesophageal Reflux Disease Questionnaire (GerdQ) were performed before and after the successful eradication of HP, and the data were compared using statistical analysis. Results Sixty-eight patients diagnosed with both GERD and HP were included. The After HP eradication group showed significantly decreased median distal contractile integral (DCI) [610.40 (847.45) vs. 444.90 (559.60)] and significantly increased median inefficient esophageal motility (IEM) [36.00 (50.00) vs. 60.00 (57.00)] in the HRM compared with those of the Before HP eradication group, indicating that HP eradication reduced esophageal peristalsis. The 24-h esophageal pH monitoring showed that the longest reflux event, the percentage of time that the pH was <4, the number of reflux episodes, and the DeMeester score were all significantly different between the Before and After HP eradication groups (P < 0.05), suggesting that HP eradication increased esophageal acid exposure. The After HP eradication group also had a significantly higher GerdQ score than that of the Before HP eradication group (P < 0.05). Conclusions HP eradication reduced esophageal peristalsis, enhanced esophageal acid exposure, and aggravated GERD symptoms, suggesting that HP infection may be a protective factor for GERD.